PENGEMBANGAN MEDIA PEMBELAJARAN VIRTUAL REALITY PADA MATERI PENGENALAN TERMINATION DAN SPLICING FIBER OPTIC - Irnando Arkadiantika; Wanda Ramansyah; Muhamad Afif Effindi; Prita Dellia (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2020)
Good learning process must contain interactive, fun, motivating aspects and provide more space for students. Need to be considered in the selection of media, among others, learning objectives, effective, easy to obtain learners, usage is not stiff, cost, and quality. One of the recent developments in learning media is the learning media using Virtual Reality. Virtual Reality is an application where users will experience the artificial world based on its original form. This research aims to produce learning Virtual Reality media learning in the material of fiber optic splicing and termination in Informatics Education Study Program. This research is a development study using 4D model consisting of 4 stages: (1) define; (2) design; (3) develop; and (4) disseminate. Testing in this study involved material experts, media experts, individuals (3 students), small groups (9 students), and large groups (22 students). Testing result by expert in course reached 75% (media). Testing result by media expert validation reached 97.5% (very valid). Individual trial results with a percentage of 84.17% (valid). Small group trial results with a percentage of 83.33% (valid). Large group trial results with a percentage of 84.55% (valid). From the testing results it could be concluded the learning media very proper to implement in learning.